Pengaruh Temperatur Proses Curing Terhadap Sifat Thermal Komposit Epoksi Berpengisi Nanopartikel Sn-3.5Ag - Tri Partuti; Yanyan Dwiyanti; Adhitya Trenggono; Fuji Utari (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
Electrically Conductive Adhesive (ECA) is an alternative solder substitute that does not contain Pb. In this research, we made nanocomposite from epoxy resin as matrix and Sn-3.5Ag nanoparticle as filler to determine the nanocomposite thermal properties for ECA applications. We used curing process temperature variations of 30, 65 and 95 oC with sonication for 30 minutes. Differential Scanning Calorimetry (DSC) analysis showed an increase of glass transition temperature (Tg) and degradation temperature (Td), decreasing curing temperature (Tcuring) as the curing process temperature increased while the melting temperature (Tm) and crystallization temperature (Tc) tend to be constant. Tg for curing process 30, 65 and 95 oC was 35.58; 37.41 and 43.77 oC respectively. Td for curing process 30, 65 and 95 oC was 335.01; 337.50 and 342.49 oC. Tcuring in the curing process 30 and 65 oC was 179.95 and 176.08 oC. Thermogravimetric Analysis (TGA) showed that nanocomposite Td between 330-340 oC.